Neonatal Gastric Lactobezoar: Management with N-Acetylcysteine. (2nd December 2012) - Bajorek, Sarah; Basaldua, Roel; McGoogan, Katherine; Miller, Charla; Sussman, Craig B.
Abstract : Gastric lactobezoars (GLBs) are the most common form of bezoars in neonates and consist of aggregations of undigested milk constituents. GLB can present with a variety of intra-abdominal clinical symptoms, and occasionally, extra-abdominal symptoms. Conservative management, with a period of bowel rest and intravenous fluids, is the most common treatment regimen for uncomplicated GLB. Surgical measures are reserved for the rare complications of obstruction and/or perforation. Although limited, utilization of the protein-cleaving enzyme N-acetylcysteine has been described for the disintegration of GLB in toddlers. In this paper, we discuss the first documented use of N-acetylcysteine for a neonatal GLB. Supporting literature, the infant's unusual presentation, and details of the treatment regimen are discussed.